Successful Treatment of Colorectal Anastomotic Stricture by Using Sphincterotomes - Chen, Tzu-An; Hsu, Wei-Lun (Frontiers in Surgery, 2014)
Colorectal or colocolic anastomotic stricture is a common complication after colorectal surgery. Traditionally, endoscopic balloon dilation technique was used for those patients with symptomatic stricture. The use of electroincision (radial incisions of the scar) along with pneumatic balloon dilation was reported with good result in literature. We present a novel method for relieving colorectal anastomotic stricture by using sphincterotomes, which is indicated for use in the cannulation of the biliary ducts and the transendoscopic sphincterotomy of the papilla of Vater and the sphincter of Oddi. The use of sphincterotomes in upper GI tract anastomotic stricture were reported before, but the experience in managing lower GI tract was pending. Based on our preliminary report, sphincterotomes can be an effective and safe treatment option for colorectal anastomotic stricture.